h-Stability for Differential Systems Relative to Initial Time Difference - Peiguang Wang; Xiaowei Liu (Abstract and Applied Analysis)
This paper investigates the relationship between an unperturbed differential system and a perturbed differential system that have initial time difference. Notions of h-stability for differential systems with initial time difference are introduced, and stability criteria are formulated by using variation of parameter techniques.